2006
DOI: 10.1007/s00198-006-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Can you diagnose for vertebral fracture correctly by plain X-ray?

Abstract: The correct diagnosis rate for incident vertebral fractures with X-Ps was low (24.8%) and in cases with prevalent fractures, the rate was even lower (16.8%), but the number of prevalent fractures and BMD did not exert an effect. One key improving the correct diagnosis rate may be to pay attention to morphological changes in the anterior bone cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
0
22
1
5
Order By: Relevance
“…Hairline fractures or non-displaced fractures are difficult to detect on conventional radiographs. In patients with osteoporosis, a wrong diagnosis of latent vertebral fracture is often made when it is based on plain X-ray imaging [22]. In the cervical spine, plain X-ray films detect only 60-80% of fractures; a significant number of fractures are not visible, even when three views of the spine are obtained [23].…”
Section: Plain X-ray Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hairline fractures or non-displaced fractures are difficult to detect on conventional radiographs. In patients with osteoporosis, a wrong diagnosis of latent vertebral fracture is often made when it is based on plain X-ray imaging [22]. In the cervical spine, plain X-ray films detect only 60-80% of fractures; a significant number of fractures are not visible, even when three views of the spine are obtained [23].…”
Section: Plain X-ray Filmsmentioning
confidence: 99%
“…At the time of injury, the average age of patients with traumatic spine lesions is 32 years and 55% of those injured are aged [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] years. Approximately, half of spinal injuries occur in the cervical spine, the other half involves the thoracic, lumbar, and sacral areas.…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended that in severe spinal trauma CT should be the first imaging modality 10 . In the cervical spine, plain radiography detect only 60-80% of fractures; a significant number of fractures are not visible, even when three views of the spine are obtained 10,11 . Despite of the limitation, Radiography remains appropriate in low-risk subjects, as well as in those situations where CT is not available.…”
Section: Introductionmentioning
confidence: 98%
“…Plain radiography, even with the best possible technique, underestimate the amount of traumatic spine injury, and abnormalities may be missed. It has been shown that 23-57% of spinal fractures are missed by standard radiography compared to multi-detector (multislice) Computed tomography (CT) 9 . It is recommended that in severe spinal trauma CT should be the first imaging modality 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Plain dynamic loading radiography involves taking images of the lateral surface of the vertebral body in both postures and calculating changes in vertebral height between the two. This method is believed to significantly improve the accuracy of the diagnosis of fresh fractures at the time of the first visit [5] compared to conventional bidirectional plain radiography, which is performed in the supine position for anterior-posterior imaging and in the side-lying non-loaded position for lateral imaging [17]. In addition, by using images obtained from plain dynamic loading radiography to measure differences in vertebral collapse rate in the standing/sitting and supine position, instability of the fractured vertebral body in a loaded posture and non-loaded posture can be evaluated.…”
Section: Introductionmentioning
confidence: 99%